Registros de nidadas de cuatro huevos y cuatro pichones de Chiflón (Syrigma sibilatrix) en Argentina - Salvador, Sergio; Fiorucci, Miguel; Santillán, Miguel Ángel; Liébana, María Soledad (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.